Relationship Between Knowledge Levels Donors Age 17-30 Years Old And Routine Blood Donation At UTD PMI Surabaya - Widuri, Sasi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The sampling technique in this study is Simple Random Sampling. From the routine results on 80 respondents showed that there were 36 respondents (45%) did blood donor routines and as many as 44 respondents (55%) did not do blood donor routines at UTD PMI Surabaya and from the Chi Square test using SPSS obtained a correlation coefficient value of 0.649 because Asymp.sig value 0.649> 0.05, so based on the research hypothesis it can be concluded that if the p value α (0.05) then Ho is rejected and Ha is accepted, which means there is no significant relationship between the level of knowledge of donors aged 17 - 30 years with routine blood donor at UTD PMI Surabaya in this study. That there is no significant relationship between the level of knowledge of donors aged 17 - 30 years with the routine blood donor at UTD PMI Surabaya in this study